Dopamine-functionalized sulphated hyaluronic acid as a titanium implant coating enhances biofilm prevention and promotes osseointegration. Issue 7 (9th August 2018) - Guarise, Cristian; Barbera, Carlo; Pavan, Mauro; Pluda, Stefano; Celestre, Micol; Galesso, Devis
Abstract: A series of new hyaluronan derivatives was synthesized and tested as an antibiotic release system by antibacterial and osseointegration assays. Specifically, partially sulphated hyaluronic acid (sHA) was functionalized with dopamine (DA). The DA moiety guarantees good performance as a binding agent for coating a titanium alloy surface; furthermore, the negatively charged sHA has bone regenerative effects and a high binding affinity for positively charged antibiotics. A sHA scaffold with a defined degree of sulphation (DS =2) was selected as a good compromise between a high negative charge density and poor heparin-like anticoagulant activity, while the degree of DA derivatization (17.1%mol) was chosen based on the absence of cytotoxic activity and the promotion of osteoblast proliferation. The titanium alloy coating was investigated indirectly using a fluorescent probe and directly by environmental scanning electron microscope (ESEM) analysis. Long-duration antibiotic release was demonstrated in vitro, and antibacterial efficacy against a Staphylococcus aureus culture was shown.